KINERJA SMA NEGERI 1 KABUPATEN KARANGANYAR PROVINSI JAWA TENGAH - Hermansyah . (Master of Public Administration, Universitas Slamet Riyadi, 2022)
An analysis of the performance of public organizations is important to findinformation as an evaluation activity in order to assess the success of theimplementation of its duties and functions. SMA N 1 Karanganyar is one of theleading public high schools in Karanganyar Regency with an A (Excellent)accreditation. This study aims to examine how the performance of SMA Negeri 1Karanganyar Regency, Central Java Province. The research used a qualitativecase study type method. The primary and secondary data, collected throughinterviews and documentation, and refers to various written sources. Thisresearch use performance analysis theory for the public sector, with indicators ofresponsiveness, responsibility, accountability, productivity, and service quality.The results found that SMA N 1 Karanganyar met good indicators in terms ofresponsiveness, responsibility, accountability, and productivity. However,limitations were found in terms of responsiveness which could still be optimized,due to limited socialization of complaint management. In addition, in terms ofservice quality, it is necessary to pay attention to empathy because there is noopen academic dialogue and public relations to collect input from the widercommunity. So, there is no better service agenda and priority based on user inputand the general public.Keyword: responsiveness, responsibility, accountability, productivity, servicequality, SMAN 1 Karanganyar